(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Present study examines the preservation and conservation of manuscripts in Assam, India, with a focus on linguistic diversity, temporal distribution, and script variations. The objectives include analyzing the linguistic diversity of manuscripts, investigating their temporal distribution, and examining script variations to understand the region’s cultural heritage.